Hereditary Hemorrhagic Telangiectasia in Pediatric Age: Focus on Genetics and Diagnosis - Cesare Danesino; Claudia Cantarini; Carla Olivieri (MDPI AG, 2023)
Hereditary Hemorrhagic Telangiectasia (HHT) or Rendu-Osler-Weber Syndrome (ROW) is an autosomal dominant vascular disease, with an estimated prevalence of 1:5000. Genes associated with HHT are ACVRL1, ENG, SMAD4, and GDF2, all encoding for proteins involved in the TGFβ/BMPs signaling pathway. The clinical diagnosis of HHT is made according to the "Curaçao Criteria," based on the main features of the disease: recurrent and spontaneous epistaxis, muco-cutaneous telangiectases, arteriovenous malformations in the lungs, liver, and brain, and familiarity. Since the clinical signs of HHT can be misinterpreted, and the primary symptom of HHT, epistaxis, is common in the general population, the disease is underdiagnosed. Although HHT exhibits a complete penetrance after the age of 40, young subjects may also present symptoms of the disease and are at risk of severe complications. Here we review the literature reporting data from clinical, diagnostic, and molecular studies on the HHT pediatric population.